Phase changes of the water hexamer and octamer in the gas phase and adsorbed on polycyclic aromatic hydrocarbons1. Issue 26 (14th July 2015) - Oliveira, Luiz Fernando L.; Cuny, Jérôme; Morinière, Maxime; Dontot, Léo; Simon, Aude; Spiegelman, Fernand; Rapacioli, Mathias
<x xml:space="preserve">Abstract</x> We investigate thermodynamic properties of small water clusters adsorbed on polycyclic aromatic hydrocarbons, which are relevant systems in the context of astrophysical and atmospheric chemistry.